The role and potential of morpholinium-based ionic liquids in dissolution of cellulose. (July 2017) - Ren, Hong-wei; Wang, Qing-hong; Guo, Shao-hui; Zhao, Di-shun; Chen, Chun-mao
Graphical abstract: Possible H-bond interactions between cellulose and [AMMor][OAc]. Highlights: The morpholinium-based ILs were synthesized for dissolution of cellulose. The Morpholinium ILs showed high dissolving ability compared to imidazolium ILs. The N-methyl-N-allyl-morpholinium acetate exhibited the highest dissolving ability among ILs. The morpholinium-based ILs showed appropriate viscosity and conductivity. Offered a cost-efficient and "green" strategy for dissolution of cellulose. Abstract: The effective dissolution of cellulose prepares for its subsequently full utilization. Ionic liquids (ILs) are attractive options for "green" dissolution of cellulose. A series of morpholinium-based ILs were synthesized and applied in dissolution of cellulose. The ultrasonic assisted saturated calcium chloride solution was used to activate cellulose. The remarkable decrease (from 87% to 65%) in crystallinity of cellulose facilitated dissolution process. The type of head-corn cations significantly increased polarity ( E T (30)) and hydrogen bond acidity ( α ) of ILs. N-Allyl-N-methylmorpholinium-based ILs showed the highest E T (30) and α (59.11 kcal mol −1 and 0.51) compared to 1-Allyl-3-methylimidazolium-based ILs (57.41 kcal mol −1 and 0.46) and 1-Allyl-3-methylpyridinium-based ILs (49.36 kcal mol −1 and 0.33) owing to the electron-rich center of oxygen in the morpholine ring. The type of anions dominated the ability to accept hydrogen bond of ILs. Formate, acetate and bisulfate contributed more hydrogen bond basicity ( β ) (0.84, 0.88 and 0.91) for N-allyl-N-methylmorpholinium-based ILs in comparison with other anions. Additionally, morpholinium-based ILs exhibited appropriate viscosity. Above-mentioned performances jointly improved the dissolution of cellulose in morpholinium-based ILs. This study demonstrated the potential of using morpholinium-based ILs as a class of efficient solvents to dissolve cellulose.